«SGLT2 INHIBITORS: RATIONALE FOR THE USE IN HEART FAILURE», RESOLUTION ON THE RESULTS OF THE PANEL OF EXPERTS WITH INTERNATIONAL PARTICIPATION, ALMATY - Abzaliyeva, S.A.; Junusbekova, G. A.; Zhirov, I.V.; Zhusupova, G.K.; Abzaliyev, K.B.; Tundybaeva , M.K.; Bazarbekova, R.B.; Raisova, A.M.; Babenko , A.Yu.; Ionin , V.A. (Interdisciplinary Approaches to Medicine, 2022)
Patients with heart failure have a high risk of developing cardiovascular complications, and prevention of thereof requires timely medical care and diagnostic assessment. An expert meeting was held with the participation of the NGO "Society of Specialists in Arterial Hypertension and Cardiovascular Prevention", NGO "Evidence-Based Cardiology", NGO "Association of Endocrinologists of Kazakhstan". On April 29, 2022 a panel of experts discussed the rationale for the use of SGLT2 inhibitors in heart failure. The EMPEROR-Reduced and EMPEROR-Preserved trials analyzed cardiovascular and renal outcomes in empagliflozin treatment in patients with and without type 2 diabetes mellitus (T2DM). Several proposals and recommendations have been adopted for further research on the cardiovascular and renal effects of empagliflozin and its use in clinical practice in patients with chronic heart failure, regardless of the presence of type 2 diabetes.At the experts meeting, issues were considered on the creation of heart failure rooms in outpatient settings and the possibility of studying the concentration of brain natriuretic peptides and performing echocardiography, including the assessment of left ventricular deformity and electrocardiography (ECG).